Pengaruh Model Pembelajaran Penemuan Terbimbing terhadap Hasil Belajar Siswa Kelas X SMAN 2 Binamu (Studi pada Materi Pokok Ikatan Kimia) - Nurhikmah Nurhikmah; Muhammad Yunus; Sumiati Side (ChemEdu, 2022)
The research was a quasi-experimental that aimed to know the effect of guided discovery learning toward students’ achievement of class X SMAN 2 Binamu. The independent variable in this research was guided discovery learning models, the dependent variable was students’ achievement on chemical bonding subject matter. The population was class X SMAN 2 Binamu consisted of 157 students that spread on six classes. Taking technique of sample was random sampling. The sample of this research consisted of two classes, namely class X1 as an experiment class with 25 students and class X2 as a control class with 25 students. The data of the research were gathered by testing the students’ achievement on chemical bonding subject matter for post-test multiple choice form which were analyzed by using t-test. Results of inferential statistical analysis were tcalculate (1,865) higher than ttable (1,671) on α ═ 0,05. Conclude that guided discovery learning model gives effected to toward student’s achievement of class X SMAN 2 Binamu on chemical bonding subject matter.